Seismic Performance Assessment of Reinforced Concrete Building in Basra and Baghdad: A Comparative Study - A. Hussain, Mohanned (University of Thi-Qar Journal of Science, 2025)
This paper aims to study the seismicity of Baghdad and Basra and compare the responses of structures in both cities. Basra and other Iraqi provinces or cities, mainly the cities that lie near or adjacent to the Iranian border to the east, experience light to moderate earthquakes from time to time. Therefore, the buildings and other structures should have enough resistance to the earthquake. This comparative study is important to know the impact of location on the structures. One of the analysis methods is called nonlinear static analysis (Pushover Analysis); in this method, the building is analyzed and then evaluated to know its performance against seismic force. In this work, pushover analysis depends on ATC 40 capacity spectrum to analyze and evaluate the  G+5 floors RC building by choosing two different locations in Iraq, Basra, and Baghdad, which lie in zone 1 and zone 3, respectively, according to the UBC 70 code  using SAP 2000 software. The results showed that the base shear of the building in Baghdad is 19% more than the base shear of the building in Basra whereas the target displacement of the building in Baghdad is 73% more than the target displacement of the building in Basra. The performance level of the building in Basra was immediate occupancy which means the building had light damage In contrast; the performance level of the building in Baghdad was life safety, which means the building had moderate damage. It is suggested to redo this work using another code to check how realistic these results are.